EFFECT OFADDITION DIFFERENT CONCENTRATION OFPAPAIN ENZYME TOWARDS CHARACTERISTIC OF REBON SHRIMP (Acetes erythraeus) PROTEIN HYDROLYSATE - Harahap, Madan Syafriadi; Suparmi, Suparmi; Dahlia, Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aims to determine the effect of addition different concentration of papain enzyme to produce protein hydrolysate of rebon shrimp(Acetes erythraeus)and to know its characteristics. The method used was experimental method, with non factorial Completely Randomized Design (CRD) consisting of 3 treatment levels, namely the addition of papain enzyme 5% (T1), 10% (T2), 15% (T3). The parameters observed were proximate (ash, protein and fat) and total amino acid analysis. The results showed that the addition 15% of papain enzyme was the best treatment with chemical composition of ash, protein and fat content was 3.41%, 84.81% and 2.39%, respectively. There were 15 types of amino acids was obtained from protein hydrolysate of rebon shrimp, where as 10 types of essential amino acids and 5 types of non-essential amino acids.Keywords: Hydrolysate, Enzyme, Proximate, Amino acid.